2018
DOI: 10.1007/s40519-018-0573-3
|View full text |Cite
|
Sign up to set email alerts
|

Structural validation of ORTO-11-ES for the diagnosis of orthorexia nervosa, Spanish version

Abstract: PurposeThe ORTO-11-ES questionnaire is a tool to assess the pathological obsession displayed by some individuals regarding healthy eating. The aims of this study were (1) to confirm the factor structure of the Spanish version of ORTO-11-ES using confirmatory factor analysis (CFA) and (2) to examine the possible association between the ORTO-11-ES score, gender and body mass index (BMI).MethodsThe sample comprised 492 students from the University of Castilla la Mancha, Spain. Of these, 280 were women (56.9%). Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…The first group maintained nine items and calculated a Cronbach alpha of α = 0.73, while the second one maintained just seven items, calculated a Cronbach alpha of α = 0.83, and confirmed a single-factor model. Finally, an adaptation to Spanish was carried out [39, 40], which confirmed a three-factor structure for an 11-item questionnaire, confirmed a Cronbach alpha of α = 0.75, and established a threshold of 25.…”
Section: Resultsmentioning
confidence: 92%
“…The first group maintained nine items and calculated a Cronbach alpha of α = 0.73, while the second one maintained just seven items, calculated a Cronbach alpha of α = 0.83, and confirmed a single-factor model. Finally, an adaptation to Spanish was carried out [39, 40], which confirmed a three-factor structure for an 11-item questionnaire, confirmed a Cronbach alpha of α = 0.75, and established a threshold of 25.…”
Section: Resultsmentioning
confidence: 92%
“…In Germany, Depa et al [26] used the DOS and reported prevalence rates of 3.3% of people with ON and 9.0% of people at risk of developing ON among German university students, while in the EEUU the prevalence rate was 8% of ON and 12.4% of people were at risk [24]. In Spain, we found that the adaptation and validation of both scales performed by Parra et al [14,27], had good psychometric properties.…”
Section: Introductionmentioning
confidence: 74%
“…However, other authors attribute these differences to the structure of the questionnaire itself rather than cultural problems [ 48 ]. Furthermore, when interpreting these results, it is important to consider that the prevalence is linked to the interpretation of different versions of a self-reported questionnaire, which have used different cut-off points [ 11 , 36 , 49 , 50 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Data collection was performed via a questionnaire prepared by the researchers. The revised questionnaire was divided into three sections: (1) Sociodemographic characteristics; (2) the Eating Disorder Inventory-2 questionnaire (EDI-2) [ 33 , 34 ]; and (3) the ORTO-11-ES [ 35 , 36 ].…”
Section: Methodsmentioning
confidence: 99%